Implementasi Pembelajaran Bermain Berbasis Lingkungan dalam Mengembangkan Aspek Perkembangan Anak Usia Dini di PAUD Mawar (Lembaga Pengembangan Kinerja Dosen, 2025)
Early Childhood Education (PAUD) emphasizes the principle of child-centered learning through meaningful and contextual play activities. Environment-based learning is one of the approaches that is relevant to the characteristics of early childhood because it provides a real learning experience and is close to the child's life. This study aims to describe in depth the implementation of environment-based play learning and its impact on cognitive, language, social-emotional, and motor development in early childhood. The research method used was qualitative descriptive with group B child subjects in PAUD Mawar. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study show that environment-based play learning is able to increase children's active involvement, curiosity, communication skills, cooperation, and motor skills. The conclusion of this study shows that environment-based play learning is effectively applied in PAUD Mawar and can be used as an alternative to contextual and holistic learning strategies.